Peran Pendidikan Islam dalam Membangun Karakter Moderasi Beragama pada Generasi Z - Mardiah, Radiatun; D, Dinizen; G, Gusmaneli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Islamic education plays a crucial role in shaping the character of religious moderation among Generation Z, serving as an effective strategy to counteract extremism and intolerance. Religious moderation within Islamic education goes beyond teaching a balanced and contextually relevant understanding of faith; it also instills values such as honesty, openness, compassion, tolerance, and respect for diversity. By integrating teachings from the Qur’an, Hadith, Aqidah, Akhlaq, and Fiqh through inclusive and moderate pedagogical approaches, Islamic education contributes to developing wise, just, and balanced young individuals capable of embracing pluralism. Consequently, Generation Z is expected not only to possess deep religious knowledge but also to live harmoniously within a diverse society. This study highlights the importance of internalizing religious moderation values as a strong foundation for character building and as a key to fostering peaceful and civilized national life.